Persepsi Mahasiswa terhadap Pemanfaatan Case Based Learning pada Mata Kuliah Wajib Umum - Ahmad Rab'iul Muzammil; Mariyadi Mariyadi; Suparjan Suparjan (MANAZHIM, 2023)
This study aims to explore the perceptions of students who take Compulsory Curriculum Courses (MKWK) courses on the application of Case Based Learning by MKWK lecturers at Tanjungpura University, especially in Indonesian Language, Islamic Religion, Catholicism, Citizenship Education, and Pancasila courses. This study applied a qualitative descriptive method with semi-structured interview data collection techniques. Using thematic data analysis techniques, this study succeeded in revealing students' perceptions of the application of the CBL learning model in MKWK lectures. They experienced a learning process in the form of affordability of knowledge towards skills, activeness in class, feelings of anxiety and a sense of empowerment, as well as professional understanding and understanding of community life. Overall students respond positively to the application of the CBL learning model.